Immunohistochemical analysis of Ki-67 in dental follicle of asymptomatic impacted third molars - Kucukkolbasi, Hasan (Medknow Publications & Media Pvt Ltd, 2014)
INTRODUCTION: Dental follicle (DF) is an ectomesenchymal tissue that surrounds the developing tooth germ and contains precursor cells for cementoblasts, periodontal ligaments and osteoblasts. Radiographically, the DFs are seen as semicircular radiolucencies around unerupted teeth. However, if the DFs are larger than 2.5 mm, they are considered to be a pathological change. AIMS AND OBJECTIVES: The purpose of this study is to assess the cell proliferation activity of DF surrounding an asymptomatic impacted third molar teeth using the Ki 67 proliferation marker and to evaluate the variation of cell proliferation depending on the age factor. MATERIALS AND METHODS: Forty-four specimens of DFs associated with impacted mandibular third molars fully covered by mucosa or bone were surgically removed from 44 patients. The patients were divided into 2 age groups. Twenty of forty-four DFs were between 18 and 29 years (Group 1) and 24 were 30 years and above (Group 2). Ki-67 immunostaining was evaluated in epithelial component of the DFs. RESULTS: Ki 67 expression was found to be 60% in Group 1 and 75% in Group 2. Statistically significant differences were found among the two groups in both the basal layer and the supra-basal layer. CONCLUSION: This study shows that DFs have more proliferative potential in older people as compared to the young and squamous metaplasia may be an early sign of developing lesions of odontogenic origin. Therefore, clinicians should be aware that histopathological changes could be found in DFs without clinical and radiographic alterations.